(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Liver cirrhosis is an end-stage manifestation of chronic liver diseases, contributing significantly to global morbidity and mortality. While liver biopsy remains the historical gold standard for staging fibrosis, its invasiveness, cost, and potential complications necessitate the integration of reliable non-invasive tests (NITs). This study aims to evaluate the diagnostic accuracy and clinical utility of serum-based non-invasive scoring systems, specifically the AST to Platelet Ratio Index (APRI) and the Fibrosis-4 (FIB-4) index, in identifying liver cirrhosis within the population of the Fergana Valley. A cross-sectional observational study was conducted involving 110 participants, comprising 75 patients with clinically and sonographically confirmed liver cirrhosis and 35 healthy controls. Routine laboratory parameters, including complete blood counts and liver function tests, were analyzed to calculate APRI and FIB-4 scores. Statistical evaluation utilized the Student’s t-test and diagnostic performance metrics (sensitivity, specificity). The results demonstrated a highly significant elevation of both scores in the cirrhotic cohort. The mean APRI score in cirrhotic patients was 1.85 ± 0.22 compared to 0.32 ± 0.05 in controls (p < 0.001). Similarly, the FIB-4 index was profoundly elevated (4.85 ± 0.55 vs. 0.95 ± 0.12, p < 0.001). Using a cut-off of >3.25, FIB-4 exhibited a sensitivity of 82% and a specificity of 89% for detecting advanced cirrhosis. Serum-based non-invasive tests, particularly the FIB-4 index, offer a highly accurate, cost-effective, and safe alternative to biopsy. Their routine implementation in regional primary care settings is critical for the early identification, risk stratification, and timely management of patients with progressive liver disease.